2010
DOI: 10.1002/eji.201040568
|View full text |Cite
|
Sign up to set email alerts
|

IL‐2‐activated haploidentical NK cells restore NKG2D‐mediated NK‐cell cytotoxicity in neuroblastoma patients by scavenging of plasma MICA

Abstract: NK group 2D (NKG2D)-expressing NK cells exhibit cytolytic activity against various tumors after recognition of the cellular ligand MHC class I chain-related gene A (MICA). However, release of soluble MICA (sMICA) compromises NKG2D-dependent NK-cell cytotoxicity leading to tumor escape from immunosurveillance. Although some molecular details of the NKG2D-MICA interaction have been elucidated, its impact for donor NK (dNK) cellbased therapy of solid tumors has not been studied. Within an ongoing phase I/II trial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
93
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(103 citation statements)
references
References 44 publications
5
93
0
5
Order By: Relevance
“…High sMICA levels coincided also with decreased survival rates in HNSCC patients potentially synergizing with high sMICB levels. 14,34 Although sMICA appears to be a trend-setting for TIEMs of neuroblastoma 17,20 and HNSCC (CURRENT STUDY) the precise contribution of individual NKG2D ligands to TIEMs has not been evaluated yet. However, the plasma levels of the different NKG2D ligands vary considerably among patients and tumor entities.…”
Section: E1055993-6mentioning
confidence: 99%
See 1 more Smart Citation
“…High sMICA levels coincided also with decreased survival rates in HNSCC patients potentially synergizing with high sMICB levels. 14,34 Although sMICA appears to be a trend-setting for TIEMs of neuroblastoma 17,20 and HNSCC (CURRENT STUDY) the precise contribution of individual NKG2D ligands to TIEMs has not been evaluated yet. However, the plasma levels of the different NKG2D ligands vary considerably among patients and tumor entities.…”
Section: E1055993-6mentioning
confidence: 99%
“…11,[17][18][19] Interestingly, we demonstrated that sMICA and transforming growth factor b 1 (TGFb 1 ) compromise the function of activated donor NK cells applied as an immunotherapeutic approach in children with neuroblastoma after haploidentical stem cell transplantation (HSCT). 20 Thus sMICA/TGFb 1 play a critical role in the immune surveillance and effector cell-mediated killing of tumor cells with respect to both patient and donor NK cells.…”
Section: Introductionmentioning
confidence: 99%
“…Marked levels of the soluble form of the MHC class I-related chain A, identified as a human NKG2D ligand, were found in the sera of patients with disseminated head-and-neck squamous cell [26] and human hepatocellular carcinomas [27] and neuroblastoma [28]. This tumor-derived soluble inhibitory ligand appears to be responsible for the downregulation of NKG2D expression in NK cells and subsequent impaired NKG2D-mediated cytotoxicity in patients with advanced disease.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, high doses of activated haploidentical NK-DLI could restore NKG2D-mediated cytotoxicity by scavenging of sMICA. 36 Pharmacological upregulation of NKG2D ligands is also being explored as a potential way of rendering blast cells more sensitive to NK cellmediated lysis. 37 Therefore, future studies should also focus on strategies to overcome these tumor immune escape mechanisms.…”
Section: Discussionmentioning
confidence: 99%